2021
DOI: 10.1186/s13054-021-03469-w
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal oxygen in patients with COVID-19-associated acute respiratory failure

Abstract: Purpose Whether the use of high-flow nasal oxygen in adult patients with COVID-19 associated acute respiratory failure improves clinically relevant outcomes remains unclear. We thus sought to assess the effect of high-flow nasal oxygen on ventilator-free days, compared to early initiation of invasive mechanical ventilation, on adult patients with COVID-19. Methods We conducted a multicentre cohort study using a prospectively collected database of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
144
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(169 citation statements)
references
References 40 publications
4
144
1
5
Order By: Relevance
“…Monitoring of patients receiving noninvasive support during acute hypoxemic respiratory failure remains of paramount importance not to delay endotracheal intubation and protective ventilation. 9 The study has several strengths: the randomized multicenter design with reproducible enrollment criteria, welldefined treatment protocols that can be applied in other intensive care units, strict prespecified criteria for defining the need for endotracheal intubation, and a process of external vali-dation by 3 independent experts to verify the adherence to such criteria for intubated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of patients receiving noninvasive support during acute hypoxemic respiratory failure remains of paramount importance not to delay endotracheal intubation and protective ventilation. 9 The study has several strengths: the randomized multicenter design with reproducible enrollment criteria, welldefined treatment protocols that can be applied in other intensive care units, strict prespecified criteria for defining the need for endotracheal intubation, and a process of external vali-dation by 3 independent experts to verify the adherence to such criteria for intubated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mellado-Artigas’ et al, demonstrated that HFNC might decrease ventilator days, ICU length of days and all-cause-hospital mortality but their cohort had lower SOFA scores, BMIs and utilized higher flows. 18 A systematic review done found that HFNC may reduce the need for IMV but there was no difference in mortality or length of stay and the studies included did not pertain exclusively to COVID-19. 19 …”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 can cause serious damage to the respiratory system, particularly with the development of pneumonia. Severe hypoxemia affected most of the patients with COVID-19 who were admitted to critical care, which makes it an important predictor of mortality in critically ill patients [ 28 ]. Therefore, clinicians should be more cautious in initially hypoxemic patients infected with SARS-CoV-2, particularly those with preexisting chronic lung disease, owing to the possibility of a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%